Improving Improving Nutrition Literacy Through Social Behavior Change Communication in Stunting Prevention Efforts in Pundu Village - Jaki, Akhmad (LP2M INSURI Ponorogo, 2025)
Stunting is a significant public health issue in Indonesia, particularly in rural areas such as Pundu Village and Kotawaringin Timur Regency. This study aims to improve community nutrition literacy through the Social Behavior Change Communication (SBCC) approach to encourage behavioral changes in stunting prevention. The research employed an initial survey to understand community conditions, followed by interpersonal communication-based socialization and community-based counseling. The findings indicate that most community members lack understanding of the importance of balanced nutrition, especially in providing proper nutrition for pregnant women and young children. The socialization activities enhanced participants' awareness of the importance of consuming nutritious food and adopting healthy lifestyles, although challenges such as limited resources and food accessibility persist. This study demonstrates that the SBCC approach effectively raises community awareness and is a strategic step for widespread application to reduce stunting prevalence in Indonesia.